EFL students’ strategies and obstacles in pronunciation self-regulated learning through TikTok: insights from Indonesian universities - Athiyatul Hidayah (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
Self-regulated learning (SRL) is crucial for mastering English pronunciation, specifically for an autonomous learning environment, including TikTok application. The present study aims to explore students’ experiences while practicing English pronunciation using TikTok as self-regulated learning. This study was designed with a qualitative case study approach. The researcher used reflection sheets and semi-structured interviews to garner data. Data were analyzed employing an interactive model. The selected participants in this research were university EFL students who learned pronunciation via TikTok. The research findings reported that the students used metacognitive strategy for independent planning, knowledge, and problem-solving for learning difficulties. Motivational strategy was also pivotal in learning pronunciation and maintaining motivation. Likewise, behavioral strategy was carried out for practicing process and shaping a conducive environment to learning activities. Nonetheless, several obstacles were encountered by the students, including lack of immediate feedback, unstructured content, low motivation, and distractions during learning. Low motivation and distraction were considered the main obstacles, which made pronunciation one of the most difficult language components in the context of SRL. This study provides practical implications for how TikTok application benefits students’ pronunciation skills, especially in self-regulated learning.